Examining the adoption of Sukuk al-Ijarah for economic development in Libya - Sharif, Abdulrahman Ateeyah (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
In today's global finance environment, Sukuk has been adopted by several governments as an alternative Islamic monetary policy tool other than bond that generate its profits from the imposition of interest. This study pinpoints financial issues faced by government of Libya and introduces Ijarah Sukuk as a solution. These issues can be summarised into two; the first issue is the non-interest-bearing certificates of deposits held by central bank and the second issue is the liquidity crisis. The study focuses on highlighting the availability of Shari'ah, legal and technical factors that serve as an infrastructure for the adoption of Sukuk al-Ijarah in Libya to tackle these issue. This case study adopts the problem-solving approach where primary data from different governmental sources is analysed using document analysis technique to firstly; explore the main issues and challenges that the country is currently suffering from and secondly; to introduce Ijarah Sukuk as an alternative monetary policy instrument. As a way of reference and guide, the study also presents Ijarah Sukuk issuance cases from other countries which were misapplied and contradictory to Shari'ah. The findings indicated acute lack of Islamic financial products and instruments innovation despite the availability of the Shari'ah, legal and environmental infrastructure. The findings also showed that Libyan legal environment is unique in the way it has only one financial system which is Islamic. This implies that the factor of competitiveness with the conventional industry is not considered in Libya, a thing that is not available in the other cases mentioned like Bahrain and Malaysia.